Students Virtual and Social Identity in the Process of Humanities Study: the Problems of its Correction - Magadieva, Gulzida F.; Melikhova, Nazilya N.; Volov, Vyacheslav T.; Konyushenko, Svetlana M.; Garipova, Aygul A.; Karpova, Irina V.; Makarova, Elena V. (International Review of Management and Marketing, 2016)
The relevance of the research problem is reasoned by global use of Internet technologies, altering the forms of personal self-identification: a transition of the external world and human individuality in a digital code, the creation of informational imprint in space of the worldwide web, the alienation of the student youth in society, the substitution of reality by virtual world. In this direction a significant potential belongs to Humanities, studying of which contributes to the interpenetration and mutual reinforcement of students' social and virtual identification based on universal norms, values, value orientations, correction of virtual identity redundancy in real society. This article is aimed at scientifically-methodical substantiation of structure and content of pedagogical correction of higher school students' self-identification in the process of Humanities' study. The leading method in this problem study is a method of modeling of the structure and content of students' self-identification pedagogical correction in the process of humanitarian disciplines' study. The article presents the theoretical and methodological foundations of the design and implementation of student's social and virtual identity correction's model, its discursive content and mechanisms, structure and new forms' content in the process of Humanities' study. The presented materials in the article contribute to evidence-based correction of students' virtual and social identity in the process of Humanities' study and are recommended to use for teachers, methodologists, university information departments' programmers, improvement of qualification and teacher retraining courses' attendants. Keywords: Pedagogical Correction, Social Self-Identity, Virtual Self-Identity, Internet Space. JEL Classifications: A23, I23, I26